A comparative study of the effects of meclofenamate, diclofenac and placebo, in combination with physiotherapy, on the healing of acute quadriceps and hamstring muscle tears - Reynolds, Jonathan F (Division of Physiotherapy, 2018)
A double-blind, placebo controlled research technique was used to determine the effects of two non-steroidal anti-inflammatory drugs, meclofenamate and diclofenac, in combination with physiotherapy treatment, on the rate and extent of healing of acute hamstring muscle tears. Sixty patients were recruited and treated at No's 1 and 2 Military Hospitals in Voortrekkerhoogte and Wynberg, Cape Town, respectively. Patients were randomly allocated to one of three treatment groups: meclofenamate, diclofenac and placebo. Patient assessments were performed on days 1, 3 and 7 of the 7-day study period. These assessments included pain assessment (visual analogue scale), swelling measurement (thigh circumference measurement at the site of the muscle tear) and muscle performance test (Cybex isokinetic dynamometer and data reduction computer). All patients received physiotherapy treatment on all 7 days of the study. This comprised early rest, ice, compression and elevation (RICE), and later, ultrasound and deep transverse friction massage. An intensive regime of strengthening and stretching exercises was used throughout the study, beginning with stretching and isometric exercises gradually moving onto isotonic exercises and aerobic exercise including swimming, running and cycling. No competitive sport was allowed during the study period. Statistical significance was determined using the analysis-of-variance (ANOVA) test with an acceptance level of p<0.05. No differences in pain, swelling or muscle performance were demonstrated between the three treatment groups. In terms of the pain and swelling assessments, the injuries did not appear to be very severe. Accordingly, the groups were divided into severe and non-severe sub-groups and statistical significance was determined using the ANOVA test with an acceptance level of p<0.05. A significant difference was found in the severe hamstring injury sub-group. In this group, pain reduction was greater in the placebo group than in the meclofenamate group on day 7. There were no other significant differences found in this sub-group analysis. Relatively few side effects were encountered, and those encountered were mild. No patients were withdrawn from the study as a result of these adverse events. Drowsiness and gastro-intestinal disturbance were the most common side effects reported. In conclusion, the study found that no benefit was gained from the use of meclofenamate or diclofenac in combination with physiotherapeutic modalities as compared to the use of physiotherapeutic modalities on their own. Thus, the widespread use of NSAIDs in the treatment of acute muscle injuries may not be justified.